2012
DOI: 10.1016/s0140-6736(11)61931-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 receptor pathways in coronary heart disease: a collaborative meta-analysis of 82 studies

Abstract: SummaryBackgroundPersistent inflammation has been proposed to contribute to various stages in the pathogenesis of cardiovascular disease. Interleukin-6 receptor (IL6R) signalling propagates downstream inflammation cascades. To assess whether this pathway is causally relevant to coronary heart disease, we studied a functional genetic variant known to affect IL6R signalling.MethodsIn a collaborative meta-analysis, we studied Asp358Ala (rs2228145) in IL6R in relation to a panel of conventional risk factors and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
250
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(260 citation statements)
references
References 43 publications
7
250
1
2
Order By: Relevance
“…Similarly, Gupta et al reported that the association between CRP and atherosclerosis is diminished in obese persons aged 30 to 65 years 35. The role of interleukin 6 was recently corroborated by 3 mendelian‐based association studies 36, 37, 38. Single‐nucleotide polymorphisms associated with decreased interleukin 6 signaling were found to correlate with lower values of acute‐phase reactants, such as CRP and fibrinogen, with a concomitant proportional reduction in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Gupta et al reported that the association between CRP and atherosclerosis is diminished in obese persons aged 30 to 65 years 35. The role of interleukin 6 was recently corroborated by 3 mendelian‐based association studies 36, 37, 38. Single‐nucleotide polymorphisms associated with decreased interleukin 6 signaling were found to correlate with lower values of acute‐phase reactants, such as CRP and fibrinogen, with a concomitant proportional reduction in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, IL-6 and IL-1 contribute to atherosclerosis and should be considered to be therapeutic targets 158,163 . Mendelian randomization studies have shown that polymorphisms that affect IL-6 signalling are associated with lower life-time risk of cardiovascular disease 23,24 . In the MEASURE trial 165 , the IL-6 receptor blocker tocilizumab increased the concentration of HDL particles in patients with rheumatoid arthritis compared with placebo, despite an increase multicentre ENTRACTE trial 166 compared the cardiovascular safety profile of tocilizumab to that of the TNF inhibitor etanercept in >3,000 patients with moderate-to-severe rheumatoid arthritis, but the final results are not yet published.…”
Section: Consequences Of Inflammageing For Cvdmentioning
confidence: 99%
“…For example, higher levels of the acute‐phase reactant C‐reactive protein (CRP) are associated with an increased risk of developing CVD 16 and a variety of other disease end‐points 17. Studies have demonstrated that higher levels of interleukin (IL)‐6 are associated with an increased risk of coronary heart disease (CHD) 18, including studies examining long‐term exposure to elevated IL‐6 19 or functional genetic variants of IL‐6 signalling 20, suggesting that the association is causal. IL‐1 is considered a master regulator of inflammation that triggers the release of a variety of inflammatory markers through activating the IL‐1 receptor.…”
Section: Introductionmentioning
confidence: 99%